Analisis Perbandingan Algoritma Penjadwalan CPU First Come First Serve (FCFS) Dan Round Robin - Putra, Muhammad Taufik Dwi; Hidayat, Haryanto; Septian, Naziva; Afriani, Tiara (Forum Kerjasama Pendidikan Tinggi, 2021)
CPU scheduling is important in multitasking and multiprocessing an operating system because of the many processes that need to be run in a computer. This causes the operating system to need to divide resources for running processes. CPU scheduling has several algorithms in it such as First Come First Serve (FCFS), Shortest Job First (SJF), Priority Scheduling, and Round Robin (RR) algorithms. The writing of this study is intended to compare the First Come First Serve and Round Robin algorithms with four specified parameters namely Average Turn Around Time, Waiting Time, Throughput, and CPU Utilization. The experiment was conducted with the First Come First Serve algorithm and the Round Robin of three different Quantum Times. These calculations at different quantum times aim to find out if the differences affect the advantages of the Round Robin algorithm over the First Come First Serve algorithm. The conclusion is that the First Come First Serve (FCFS) algorithm is superior to the Round Robin (RR) algorithm. This is indicated by the average turn around time, waiting time, and throughput values of the First Come First Serve algorithm more effective in running the process